Breast cancer is associated with coronary heart disease: a cross-sectional survey of NHANES 1999–2018 - Dai, Luyao; Li, Ruoxuan; Hao, Qian; Bao, Yuanhang; Hu, Liqun; Zhang, Yaohui; Kang, Huafeng; Wu, Hao; Ma, Xiaobin; Song, Yafan (Frontiers in Cardiovascular Medicine, 2023)
Background: Understanding the correlation between female breast cancer (BC) and the prevalence of coronary heart disease (CHD) is important for developing prevention strategies and reducing the burden of female social disease. This study aimed to evaluate the relationship between BC and CHD using data from the National Health and Nutrition Examination Survey (NHANES) database from 1999-2018.The study cohort included 16,149 eligible non-pregnant female participants aged 20 years or older. Logistic regression was used to analyze the relationship between BC and CHD, excluding the interaction between covariates and BC through hierarchical subgroup analysis.The study found that participants with BC had a 2.30 times greater risk of developing CHD compared to those without BC (95% confidence interval (CI): 2.29-2.31). After adjusting for all included covariates, BC was still significantly associated with CHD risk (odds ratio: 1.11, 95% CI:1.10-1.12). When participants were stratified by age, education level, and prevalence of hypertension, it was evident that participants with BC had a higher risk of developing CHD compared to those without BC, although the effect of BC on CHD varied across stratification.Our study demonstrates the close relationship between CHD and female BC. Therefore, it is necessary to screen patients with CHD for BC and monitor BC survivors for the long-term risk of developing CHD.